Implementing quality in hospitals – stakeholders’ roles: A qualitative social network analysis - Mabena, Sphiwe Y.; Armstrong, Susan J. (Health SA = SA Gesondheid, 2025)
Background: The current experience of the implementation of quality standards policy in South Africa has sometimes produced negative results because of insufficient understanding of policy goals, resource constraints, and a lack of consultation and involvement of the key actors. Understanding how the actors operate in the health establishments will assist stakeholders in improving compliance. Aim: This study aimed to examine the roles of actors responsible for the implementation of the six key performance areas of the National Core Standards (NCS) in the better- and least-performing hospitals in Gauteng. Setting: This study was conducted at two tertiary hospitals in Gauteng province. Methods: A qualitative social network analysis (SNA) using Net-Map was conducted with purposively selected staff to identify key actors, relationships and influence in implementing the NCS. Participants mapped actors using coloured nodes, arrows and influence towers. Data, including direct quotes, were collected through guided sessions and transcribed, revealing power dynamics and communication flows within two Gauteng tertiary hospitals. Results: Social network analysis revealed that one of the hospitals had a collaborative network with active chief executive officer (CEO) involvement, while another hospital followed a more hierarchical structure. Both were bounded networks with quality managers as key actors. Informal relationships enhanced coordination and compliance. Actor influence, connectivity and leadership engagement were critical in implementing the NCS, highlighting SNA’s value in diagnosing organisational strategy and performance gaps. Conclusion: Leadership support and shared interest with all other actors responsible for policy implementation are essential if the healthcare establishment is to comply with NCS. Contribution: Social network analysis can reveal bottlenecks, identify influential individuals and inform strategies for enhancing organisational effectiveness.